Tychius caldarai nov. spec. aus der Verwandtschaft des T. cinnamomeus Kiesenwetter (Coleoptera, Curculionidae). - Dieckmann, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 1986)
T. caldarai nov. spec. is separated from Tychius cinnamomeus Kiesenwetter, presented on the Iberian Peninsula and in southern France. The Area of T. caldarai nov. spec. includes Italy, south-eastern Central Europe and the Balkan Peninsula. Nomenclatural Acts caldarai Dieckmann, 1986 (Tychius), spec. n.